Demographic Study of Dermatological Manifestations of DM Patients Attending in a Medical College Hospital (Medicine Today, 2022)
Introduction: Diabetes mellitus (DM) is a common metabolic disorder and is significant for its ability to adverse effect of various organs. Skin manifestations in this condition are due to metabolic derangements, chronic complications and infections, which are commonly observed after developing clinical diabetes mellitus, but may also precede the disease.Aim: The aim of this study was to understand dermatological manifestations in diabetes mellitus relation with demographic parameters.Materials and Methods: It was a hospital based cross sectional study carried out among 80 randomly selected diabetic patients with/without skin lesions. Patients were then asked for their willingness to participate in the study. Skin examination was carried out and skin lesions were identified. All data was recorded in the pre-designed, pre-tested, and semi-structured questionnaire developed for the study. Data was analyzed using SPSS version 26. Frequencies and percentages were calculated for the necessary data.Result: : Mean age of the subjects was 51.0±13.2 years, minimum age 25 and maximum 80 years. It was observed that, out of 80 patients, 52 (65.0%) were aged between 41–60 years. 52 (65%) were female and 28(35%) were male patients. 46(57.5%) were housewives and 16(20.0%) were service holders, 10(12.5%) were farmers and other 8(10%). 41(51.2%) from middle class, 38(47.5%) from lower class and 1(1.3%) were from upper class. 61.2% patients came from rural area and 38.8% patients from urban area. The mean duration of diabetes mellitus was 6.6±5.1 years, 42.5% patients duration had 5-10 years followed by 36.3% below 5 years and 21.3% patients had DM more than 10 years. Out of 80 patients, a total of 39(48.8%) DM patients had skin manifestations and 41(51.2%) had no skin manifestations. Among 39 DM patients with skin disease, 19(48.7%) having a single, while 8(25.5%) had two and 13(30.8%) patients had three or more skin lesions. 22(56.4%) patients found diabetic dermopathy, diabetic foot ulcer 12(30.8%), fungal infections 9(23.1%), bullous lesions 7(17.9%), diabetic foot gangrene 5(12.8%), lypodystrophy 5(12.8%), pruritus 5(12.8%), xerosis 5(12.8%) cases, scleredema 3(7.7%), ichthyosis 2(5.1%) and bacterial infections 2(5.1%). Age, sex, educational level, socioeconomic status, residence found no significant association (p>0.05), but duration of diabetes mellitus was significantly associated with the presence of dermatological manifestations (p=0.001).Conclusion: The spectrum of skin manifestations due to DM in this study population is similar to that in other parts of the world. Diabetic dermopathy, Pruritus and fungal infections are the most common cutaneous manifestations in DM patients. The presence of skin manifestations can highlighten the suspicion for DM enabling early diagnosis and management and thereby can be helpful for preventing complications.Medicine Today 2022 Vol.34(2): 145-149